Primary isolation strain determines both phage type and receptors recognised by Campylobacter jejuni bacteriophages. - Martine C Holst Sørensen; Yilmaz Emre Gencay; Tina Birk; Signe Berg Baldvinsson; Claudia Jäckel; Jens A Hammerl; Christina S Vegge; Horst Neve; Lone Brøndsted (PLoS ONE, 2015)
In this study we isolated novel bacteriophages, infecting the zoonotic bacterium Campylobacter jejuni. These phages may be used in phage therapy of C. jejuni colonized poultry to prevent spreading of the bacteria to meat products causing disease in humans. Many C. jejuni phages have been isolated using NCTC12662 as the indicator strain, which may have biased the selection of phages. A large group of C. jejuni phages rely on the highly diverse capsular polysaccharide (CPS) for infection and recent work identified the O-methyl phosphoramidate modification (MeOPN) of CPS as a phage receptor. We therefore chose seven C. jejuni strains each expressing different CPS structures as indicator strains in a large screening for phages in samples collected from free-range poultry farms. Forty-three phages were isolated using C. jejuni NCTC12658, NCTC12662 and RM1221 as host strains and 20 distinct phages were identified based on host range analysis and genome restriction profiles. Most phages were isolated using C. jejuni strains NCTC12662 and RM1221 and interestingly phage genome size (140 kb vs. 190 kb), host range and morphological appearance correlated with the isolation strain. Thus, according to C. jejuni phage grouping, NCTC12662 and NCTC12658 selected for CP81-type phages, while RM1221 selected for CP220-type phages. Furthermore, using acapsular ∆kpsM mutants we demonstrated that phages isolated on NCTC12658 and NCTC12662 were dependent on the capsule for infection. In contrast, CP220-type phages isolated on RM1221 were unable to infect non-motile ∆motA mutants, hence requiring motility for successful infection. Hence, the primary phage isolation strain determines both phage type (CP81 or CP220) as well as receptors (CPS or flagella) recognised by the isolated phages.